Analisis Tren K-pop terhadap Motivasi Belajar Bahasa Inggris di Kalangan Gen-Z - Rahma Arifatuzzahra; Maila Syakhshiyatul Ma’rufah; Annisa Sultan Alfiani; Amalia Fajriyyatin Najichah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
This research analyzes the impact of the K-pop trend on motivation to learn English among Gen-Z. The study identified that the importance of English for educational and career purposes encourages Gen-Z to learn it. However, there are factors that contribute to decreased motivation, such as uninteresting learning materials, social stigma, lack of confidence, and time constraints. In recent years, the K-pop phenomenon has provided an interesting and non-monotonous approach to learning English. Gen-Z is inspired to learn English through K-pop content on platforms such as YouTube, TikTok and Instagram. In addition, fandom interactions on social media require English as the language of communication. K-pop idols also actively interact with fans in English through YouTube channels and live streaming apps. The presence of English subtitles in K-pop content, the use of English lyrics in songs, and the use of English platforms by idol agencies further increase the motivation to learn English among Gen-Z. This research aims to provide a comprehensive analysis of the impact of K-pop trends on Gen-Z's motivation to learn English as well as the factors that contribute to this motivation. The results of this study are expected to deepen our understanding of the relationship between the K-pop trend and motivation to learn English, as well as facilitate the understanding of the relationship between the K-pop trend and motivation to learn English. and facilitate the development of effective language learning strategies